IMPLEMENTASI PENGEMBANGAN KURIKULUM MADRASAH BERTARAF INTERNASIONAL (MBI) DI MTS TAHFIDZ YANBU’UL QUR’AN MENAWAN KUDUS - Miftakhul Himawan; Muhammad Setya Aji; Naila Amanyya Muhibin; Muhammad Sholihuddin (STIKes Ibnu Sina Ajibarang, 2025)
In facing the challenges of the dichotomy of knowledge in the modern era, madrasas as Islamic educational institutions need to adjust the curriculum design that is relevant to the changing times, one form of development is by implementing an international standard madrasa curriculum. The purpose of this study is to reveal the strategies, challenges, obstacles and implications in implementing the development of a madrasa curriculum with international standards at MTs Tahfidz Yanbu'ul Qur'an Menawan Kudus. This study applies a Qualitative approach that is a case study, with data collection carried out through interviews, observations, and related documents. The findings of this study indicate that the method of implementing the curriculum at MTs Tahfidz Yanbu'ul Qur'an Menawan Kudus is formed from the integration of the Foundation curriculum, the Ministry of Religion, and the Innovative Curriculum which is then accumulated into intracurricular and extracurricular activities. The challenges and obstacles are caused by limited human resources, both teachers and student abilities. The implications for students are that it is able to produce students who have memorized the Qur'an and excel in the fields of foreign languages, research, science and technology, as shown by increased achievements in olympiads, science and robotics competitions.